Role of Triphala on Gut Microbiota in the Treatment of Obesity and its Complications (International Journal of Ayurveda and Pharma Research, 2024)
Obesity is a rapidly increasing global public health concern with a prevalence of 40.3% in India. Obesity is also a significant risk influence for ailments including hypertension, dyslipidaemia, diabetes, coronary heart condition, osteoarthritis, cancer and mental illness. This review investigates the potential role of Triphala in the treatment of obesity and its complications on gut microbiota. Method: We selected relevant articles after searching Scopus, PubMed and Google Scholar using keywords Triphala, Obesity, DM, CVD, and Gut microbiota. Obesity and related complications are considered by definite changes within the human gut microbiome. The gut microbiota of individuals with obesity contains lower proportions of Bacteroidetes and greater amounts of Firmicutes. Gut microbiota modulation and revitalization are emerging as potential obesity prevention and/or treatment strategies via probiotics, prebiotics, synbiotics, or faecal transplants. Research showed that butyrate generating bacteria like Faecalibacterium prausnitzii and Akkermansia muciniphila, were greatest in normal people, but that Bacteroides were halved in diabetes patients. The host metabolic syndrome and cardiovascular risk may be influenced by lipopolysaccharides (LPS) from gut microbiota. A placebo-controlled trial concluded that Triphala includes a hopeful role in reducing weight, circumferential measures and body fat. Triphala's prebiotic effect was studied using in vitro batch cultures, fruit fly, and a simulated model of the human alimentary tract, where Triphala promoted the growth of good bacteria while inhibiting pathogenic species in each model. Clinical research is still under progress on the effect of Triphala on Stool Microbiome Profiles and Inflammation. The action of Triphala in altering the gut microbiota for effective management of obesity and its complications is yet to be studied. Here we recommend the potential action of Triphala in managing obesity and its complications by targeting gut microbiota.